Role of the intestinal microbiome in colorectal cancer surgery outcomes - Lelde Lauka; Elisa Reitano; Maria Clotilde Carra; Federica Gaiani; Paschalis Gavriilidis; Francesco Brunetti; Gian Luigi de’Angelis; Iradj Sobhani; Nicola de’Angelis (World Journal of Surgical Oncology, 2019)
Abstract Objectives Growing evidence supports the role of the intestinal microbiome in the carcinogenesis of colorectal cancers, but its impact on colorectal cancer surgery outcomes is not clearly defined. This systematic review aimed to analyze the association between intestinal microbiome composition and postoperative complication and survival following colorectal cancer surgery. Methods A systematic review was conducted according to the 2009 PRISMA guidelines. Two independent reviewers searched the literature in a systematic manner through online databases, including Medline, Scopus, Embase, Cochrane Oral Health Group Specialized Register, ProQuest Dissertations and Theses Database, and Google Scholar. Human studies investigating the association between the intestinal microbiome and the short-term (anastomotic leakage, surgical site infection, postoperative ileus) and long-term outcomes (cancer-specific mortality, overall and disease-free survival) of colorectal cancer surgery were selected. Patients with any stage of colorectal cancer were included. The Newcastle-Ottawa scale for case-control and cohort studies was used for the quality assessment of the selected articles. Results Overall, 8 studies (7 cohort studies and 1 case-control) published between 2014 and 2018 were included. Only one study focused on short-term surgical outcomes, showing that anastomotic leakage is associated with low microbial diversity and abundance of Lachnospiraceae and Bacteroidaceae families in the non-cancerous resection lines of the stapled anastomoses of colorectal cancer patients. The other 7 studies focused on long-term oncological outcomes, including survival and cancer recurrence. The majority of the studies (5/8) found that a higher level of Fusobacterium nucleatum adherent to the tumor tissue is associated with worse oncological outcomes, in particular, increased cancer-specific mortality, decreased median and overall survival, disease-free and cancer-specific survival rates. Also a high abundance of Bacteroides fragilis was found to be linked to worse outcomes, whereas the relative abundance of the Prevotella-co-abundance group (CAG), the Bacteroides CAG, and the pathogen CAG as well as Faecalibacterium prausnitzii appeared to be associated with better survival. Conclusions Based on the limited available evidence, microbiome composition may be associated with colorectal cancer surgery outcomes. Further studies are needed to elucidate the role of the intestinal microbiome as a prognostic factor in colorectal cancer surgery and its possible clinical implications.